Latency and amplitude of P300 using speech and non-speech stimuli - a normative study - Ramteke, Bhimraj B.; Meshram, Sushil N. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The P300 was among the first auditory response in a collection of events related or endogenous evoked responses. The P300 is related to cognition and use of knowledge about the environment. Methods: The subjects (n=60) selected with an equal distribution of genders. P300 evoked potentials elicited by non-speech and speech stimuli is recorded. Results: There is a significant difference in latency of P300 for speech verses non-speech stimuli as well as there is a significant difference in the latency of P300 among males and females for speech versus non speech stimuli. No significant difference in amplitude of P300 for speech versus non-speech stimuli and for right versus left ears. Conclusions: P300 latency is influenced by stimulus used and gender variation. The present study showed that the non-speech stimuli had lower latencies compared with speech stimuli. For the P300 amplitude values, the difference between groups were not significant.